THE IMPLEMENTATION OF HANGING BALL EXERCISE FOR IMPROVING KEDENG SMASH ABILITIES IN TAKRAW LEARNING - Yarmani Yarmani; Syafrial Syafrial; arwin arwin (UNIB Press, 2020)
This study aims to apply the hanging ball exercise to improving kedeng smash ability in sepak takraw learning. This research method uses applied research, one of the studies uses a classroom action research approach. The sample used in this study is 33 students of Physical Education’s soccer takraw course. The research procedure is cycle form. Each cycle consists of four stages including: planning, implementing actions, observing and reflecting. Data collection technique through observation and test. This data collection uses observation sheets instruments of student and lecturers' performance in the learning process, to determine the quality of student learning outcomes used an evaluation or test sheet. The results showed that the application of hanging ball exercises in improving the ability to kedeng smash in sepak takraw learning can improve student learning outcomes in sepaktakraw courses from an average pre-cycle value of 10 points (50%), to 15 points (80%) in cycle 1 and the average value of 12 points prasiklus (60%), to 16 points (85%) in cycle 2.